Do budget deficits ‘crowd out’ private investment? (2007)
The present worldwide recession is proving unusually stubborn. Large reflationary packages, involving cuts in taxation and higher public spending, have been announced in several leading Western economies, but the recovery so far has been fitful and uncertain. Accompanying the sluggishness of activity have been large public sector financial deficits, particularly in the United Kingdom, the United States and West Germany. These deficits were largely caused by the recession (as it has cut tax receipts), but at the same time they are seen as serving the benign function of combating the weakness of spending (because the deficits represent a demand injection into the economy).